2017
DOI: 10.1007/s00268-017-3874-1
|View full text |Cite
|
Sign up to set email alerts
|

When Surgical Resources are Severely Constrained, Who Receives Care? Determinants of Access to Orthopaedic Trauma Surgery in Uganda

Abstract: Limited infrastructure, trained personnel, and surgical supplies rations access to surgical care. In this environment, participants with advantageous social connections were able to self-advocate for surgery where demand for these services greatly exceeded available resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…These included combining data sources, in particular adding in-depth qualitative methods for deepening understanding. 79 86 133 Widespread use of tools used in WHO ETC and WHO Tool for Situational Analysis to Assess Emergency and Essential Surgical Care-based assessments was seen as strengths, demonstrating their applicability and comparability across locations and countries. 89 98 100 140 146 147 The inclusion of a variety of sectors, professions and patients in studies was seen by study authors as positive.…”
Section: Resultsmentioning
confidence: 99%
“…These included combining data sources, in particular adding in-depth qualitative methods for deepening understanding. 79 86 133 Widespread use of tools used in WHO ETC and WHO Tool for Situational Analysis to Assess Emergency and Essential Surgical Care-based assessments was seen as strengths, demonstrating their applicability and comparability across locations and countries. 89 98 100 140 146 147 The inclusion of a variety of sectors, professions and patients in studies was seen by study authors as positive.…”
Section: Resultsmentioning
confidence: 99%
“… 7 Stephens et al found that only 58% of patients admitted with the intention of definitive T&O surgical care received surgery due to resource constraints. 8 Deficient surgical equipment and supplies often limit access to surgical care. The WHO guidelines for essential trauma care has also recognised the need for a specific equipment list.…”
Section: Introductionmentioning
confidence: 99%
“…In answering the question, “When surgical resources are severely constrained, who receives care?”, Stephens and colleagues found that patients with advantageous social connections (friends, family, and contacts affiliated with the hospital) were able to self-advocate for orthopedic trauma surgery at a national referral hospital in Uganda. This provides grounds for disparity in progression to surgery [ 41 ].…”
Section: Search Resultsmentioning
confidence: 99%